Intrafamilial segregation analysis of the p.E148Q MEFV allele in familial Mediterranean fever. Issue 9 (26th January 2006) - Tchernitchko, D O; Gérard-Blanluet, M; Legendre, M; Cazeneuve, C; Grateau, G; Amselem, S
Abstract : Background: Familial Mediterranean fever (FMF) is the most frequent of the recurrent inherited fevers. This autosomal recessive disorder is characterised by periodic episodes of fever and serositis that commonly affect the people of Arab, Armenian, Sephardic Jewish and Turkish origin. Most of the described MEFV gene anomalies responsible for the disease are missense mutations. In the absence of any functional test, epidemiological studies or pedigree analyses are the only means of proving the deleterious character of these sequence variations. Evidence was provided by our recent study using a population-based approach, that the p.E148Q allele is probably a benign polymorphism and not a disease-causing mutation. Its implication in FMF remains, however, controversial. Objective: To evaluate the segregation of the p.E148Q MEFV allele with FMF disease by using pedigree analysis. Participants: 21 patients and 48 unaffected relatives belonging to 18 independent families with FMF. Results: Segregation analysis of the p.E148Q allele was compatible with a Mendelian autosomal recessive transmission of the disease phenotype in only three families. In 15 of 18 families, segregation was partly or completely defective. The p.E148Q allele was not transmitted to 14 of 19 (74%) affected children. Conclusions: No evidence of preferential transmission of p.E148Q from heterozygous parents to their affected offspring was observed. MEFV is not associated with the clinical manifestations of several patients carrying this variant. Considering p.E148Q to be a benign polymorphism should reduce the possibility of false-positive diagnoses, while highlighting genetic heterogeneity in FMF.